Cartographic (re)presentations of local space: artistic maps adrift from School Cartography - Expedito, Cassio; Seemann, Jörn (Geografares, 2014)
Based on the importance of teaching content related to the landscape that can be seen, we propose a reflection through the use of mental maps for the perception of landscape experienced by students. This claim will be defended through a case study in public schools in Barbalha in southern Ceará (Brazil). Based on the reflections of Deleuze and Guattari, we want to expose that the map is not an illustrative tracing in class, but multiple, singular, rhizomatic. Thus, we aim to unveil these geographies that are not visible in the textbook, personal geographies with their landscapes, impregnated by beliefs, ideologies and feelings that you have of the location. Keywords: cartographic (re)presentations; mental maps; Barbalha.